Design and Application of Assistive Communication APP - Guangbiao ZHAO; Fengshan OUYANG; Zhuoming CHEN (康复学报)
Objective:To observe the effect and application value of the assistive communication APP which used to help patients with speech disorders to communicate.Methods:9 patients with speech disorders were enrolled and received 3 weeks of treatment with the assistive communication APP. The patients's atisfaction scores with communication and family members' satisfaction scores with communication were recorded before and after 3 weeks of the treatment, then the average score was calculated. The data before and after the treatment were compared and analyzed.Results:The patients'satisfaction scores with communication and family members'satisfaction scores with communication were significantly increased after treatment with the assistive communication APP (P<0.05).Conclusion:The patients with speech disorders could benefit from the assistive communication APP by improving their communication with other people, so the tool may have a great application prospect.